Large magneto-thermopower in MnGe with topological spin texture - Fujishiro, Y. (Nat Commun, 2018)
Quantum states characterized by nontrivial topology produce interesting electrodynamics and versatile electronic functionalities. One source for such remarkable phenomena is emergent electromagnetic field, which is the outcome of interplay between topological spin structures with scalar spin chirality and conduction electrons. However, it has scarcely been exploited for emergent function related to heat-electricity conversion. Here we report an unusually enhanced thermopower by application of magnetic field in MnGe hosting topological spin textures. By considering all conceivable origins through quantitative investigations of electronic structures and properties, a possible origin of large magneto-thermopower is assigned to the strong energy dependence of charge-transport lifetime caused by unconventional carrier scattering via the dynamics of emergent magnetic field. Furthermore, high-magnetic-field measurements corroborate the presence of residual magnetic fluctuations even in the nominally ferromagnetic region, leading to a subsisting behavior of field-enhanced thermopower. The present finding may pave a way for thermoelectric function of topological magnets.